Mardia’s Skewness and Kurtosis for Assessing Normality Assumption in Multivariate Regression - Wulandari, Dewi; Sutrisno, Sutrisno; Nirwana, Muhammad Bayu (Universitas Islam Indonesia, 2021)
In Multivariate regression, we need to assess normality assumption simultaneously, not univariately. Univariate normal distribution does not guarantee the occurrence of multivariate normal distribution [1]. So we need to extend the assessment of univariate normal distribution into multivariate methods. One extended method is skewness and kurtosis as proposed by Mardia [2]. In this paper, we introduce the method, present the procedure of this method, and show how to examine normality assumption in multivariate regression study case using this method and expose the use of statistics software to help us in numerical calculation. Received February 20, 2021Revised March 8, 2021Accepted March 10, 2021